Experimental measurements of the shear force on surface mount components simulating the wave soldering process. Issue 1 (7th June 2021) - Carvalho, Violeta; Arcipreste, Bruno; Soares, Delfim; Ribas, Luís; Rodrigues, Nelson; Teixeira, Senhorinha; Teixeira, José C.
Abstract : Purpose: This study aims to determine the minimum force required to pull out a surface mount component in printed circuit boards (PCBs) during the wave soldering process through both experimental and numerical procedures. Design/methodology/approach: An efficient experimental technique was proposed to determine the minimum force required to pull out a surface mount component in PCBs during the wave soldering process. Findings: The results showed that the pullout force is approximately 0.4 N. Comparing this value with the simulated force exerted by the solder wave on the component ( ≅ 0.001158 N), it can be concluded that the solder wave does not exert sufficient force to remove a component. Originality/value: This study provides a deep understanding of the wave soldering process regarding the component pullout, a critical issue that usually occurs in the microelectronics industry during this soldering process. By applying both accurate experimental and numerical approaches, this study showed that more tests are needed to evaluate the main cause of this problem, as well as new insights were provided into the depositing process of glue dots on PCBs.